2019
DOI: 10.1007/s00114-019-1602-4
|View full text |Cite
|
Sign up to set email alerts
|

Roll with the fear: environment and state dependence of pill bug (Armadillidium vulgare) personalities

Abstract: Most studies on animal personality evaluate individual mean behaviour to describe individual behavioural strategy, while often neglecting behavioural variability on the within-individual level. However, within-individual behavioural plasticity (variation induced by environment) and within-individual residual variation (regulatory behavioural precision) are recognized as biologically valid components of individual behaviour, but the evolutionary ecology of these components is still less understood. Here, we tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 88 publications
0
18
1
1
Order By: Relevance
“…We did not pick up clear signs of publication bias in the studies considered, with no effect observed of whether the original publication considered variation in rIIV (see Mitchell, 2021, for full output). However, care should still be taken in interpreting these results Contrary to the prediction that field studies would show greater variance in rIIV due to reduced control over conditions (Stamps et al, 2012;Westneat et al, 2015), field studies typically appeared to have lower estimates than laboratory studies (differ- 2020; Highcock & Carter, 2014) rather than latency to emerge (e.g., Horváth et al, 2019;Stamps et al, 2012), and measures of activity were based on tracking over large spatial scales (e.g., Hertel, Niemelä, et al, 2020;Hertel, Royauté, et al, 2020) rather than tracking within an arena (e.g., Mitchell & Biro, 2017;Prentice et al, 2020).…”
Section: Meta-analysis Of CV Pmentioning
confidence: 79%
“…We did not pick up clear signs of publication bias in the studies considered, with no effect observed of whether the original publication considered variation in rIIV (see Mitchell, 2021, for full output). However, care should still be taken in interpreting these results Contrary to the prediction that field studies would show greater variance in rIIV due to reduced control over conditions (Stamps et al, 2012;Westneat et al, 2015), field studies typically appeared to have lower estimates than laboratory studies (differ- 2020; Highcock & Carter, 2014) rather than latency to emerge (e.g., Horváth et al, 2019;Stamps et al, 2012), and measures of activity were based on tracking over large spatial scales (e.g., Hertel, Niemelä, et al, 2020;Hertel, Royauté, et al, 2020) rather than tracking within an arena (e.g., Mitchell & Biro, 2017;Prentice et al, 2020).…”
Section: Meta-analysis Of CV Pmentioning
confidence: 79%
“…Therefore, the absence of defensive behaviour in some of the lizards in our experiment might be considered as a sign of tonic immobility. Tonic immobility strategy has been previously considered in personality studies (Edelaar et al 2012;Santos et al 2015;Horváth et al 2019). Our present findings hint that between-individual differences in antipredatory last resort behavioural traits might be interpreted along a tonic immobility-antipredator aggression continuum.…”
Section: Behavioural Repeatabilitymentioning
confidence: 99%
“…Hence, antipredator aggression could be seen as a 'last resort' against predation, similarly to another, yet completely opposite antipredator behavioural trait, tonic immobility (i.e. the lack of movement; see Gallup and Rager 1996;Edelaar et al 2012;Horváth et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…When an animal is repeatedly observed, its behavioral expressions can be highly variable. This within-individual variability in behavior can be categorized into phenotypic plasticity and behavioral unpredictability [1][2][3][4]. Phenotypic plasticity explains within-individual variability observed along some environmental gradients such as wind velocity, predation risk and temperature [5].…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypic plasticity explains within-individual variability observed along some environmental gradients such as wind velocity, predation risk and temperature [5]. Behavioral unpredictability (also known as "residual behavioral variance") is the remaining (residual) variability after the effects of environmental and explanatory variables are accounted for [1][2][3][4]. Although behavioral unpredictability may appear as mere noise in behavioral expressions, there are some patterns in expressions of behavioral unpredictability.…”
Section: Introductionmentioning
confidence: 99%